2014
DOI: 10.1103/physrevb.89.064106
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure transformation in CeRuSn seen via the atomic pair distribution function

Abstract: We report on the atomic pair distribution function determination in the ternary compound CeRuSn using high energy synchrotron x-ray diffraction. Above room temperature CeRuSn orders in a monoclinic structure that is related to the CeCoAl type of structure by a doubling of the c-axis parameter. Upon cooling a very broad hysteretic structural transition has been observed in CeRuSn leading to an ill-defined structure with a main component having three times larger c parameter. The pair distribution functions coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 19 publications
1
12
0
Order By: Relevance
“…The 2c structure is reported to be replaced by various structural modifications, the dominant mode being a tripling of the basic CeCoAl cell (the 3c structure). Nevertheless, our recent synchrotron x-ray work showed that the 3c structure is only an approximation to the real crystal structure of CeRuSn [13]. However, neither of the literature sources could solve the details of the low temperature crystal (and hence also the AF structure) unambiguously.…”
Section: Introductionmentioning
confidence: 98%
“…The 2c structure is reported to be replaced by various structural modifications, the dominant mode being a tripling of the basic CeCoAl cell (the 3c structure). Nevertheless, our recent synchrotron x-ray work showed that the 3c structure is only an approximation to the real crystal structure of CeRuSn [13]. However, neither of the literature sources could solve the details of the low temperature crystal (and hence also the AF structure) unambiguously.…”
Section: Introductionmentioning
confidence: 98%
“…Unfortunately, we were unable to determine structural details of our crystal at room temperature (these are available for 10 K [14]). For analysis of data taken at 285 K we have therefore utilized parameters determined from our previous x-ray single crystal diffraction and neutron powder diffraction that are in good agreement with structural information obtained by other groups [9,10,13,17]. This high-temperature crystal structure of CeRuSn projected nearly along the b axis is shown in Fig.…”
Section: B Spin Density At 285 Kmentioning
confidence: 87%
“…Since the modulation is close to a tripling of the original CeCoAl structure along the c axis, we have used the three times larger c-axis parameter. The positional parameters were taken from literature [10,13,17]. This leads to three independent Ce, Ru, and Sn sites.…”
Section: Spin Density At 2 Kmentioning
confidence: 99%
See 1 more Smart Citation
“…Further details on the structure refinement are available from Fachinfor- short Ce-Ru distances, first observed for CeRuSn [36][37][38] and several aluminides [39], gallides [40] and indides [41]. The intermediate-valent character of cerium in these intermetallics has been manifested by temperature dependent magnetic susceptibility stud-…”
Section: Structure Refinementmentioning
confidence: 98%